„Vásáron vagyunk az irodalomban”: Az 1840-es évek divatlapjainak gazdasági aspektusai - Fazekas, Júlia (Studia Litteraria, 2021)
Several economic factors contributed to the success of the Hungarian fashion magazines of the 1840s. They were widely read periodicals and they focused mainly on literature. The magazines competed to gain more subscribers and sign well-known authors. Journalism and working as an author were often tied together. Writers could make a living from publishing their works in these magazines, which was unprecedented in Hungarian literary history. Editing or working on a periodical also provided a significant source of income. This paper examines the Hungarian fashion magazines from an economic standpoint: the prots and the expenses of each periodical, the tactics publishers used to appeal to the public, while also focusing on the earned royalties and questions related to the authorial profession.